The rise of critical Islam 10th-13th century legal debate - Soufi, Youcef L. (Oxford University Press, 2023)
"In a richly narrated historical study, Soufi excavates an Islamic legal culture of critique from the 10th-13th century. Focusing on the practice of (disputation), Soufi explores how and why oral debates became a pervasive and revered part of the intellectual legal landscape of Iraq and Persia. Pushing back against claims that classical Muslim jurists sought to weed out differences of opinion, The Rise of Critical Islam presents a community committed to the openness, fluidity, and continued exploration of the law. In uncovering this classical legal culture, Soufi invites readers to question claims about the promise of secular critique in disciplining religious passions and forging human solidarity"-- Provided by publisher.
Keywords: Geschichte 900-1300; Debatte; Islam; Mündliche Kommunikation; Rechtskultur; Islamic law / History / To 1500; Islamic law / Methodology / History / To 1500